Service-Oriented Computing 9th International Conference, ICSOC 2011, Paphos, Cyprus, December 5-8, 2011 Proceedings - Kappel, Gerti; Maamar, Zakaria; Motahari-Nezhad, Hamid R. (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the 9th International Conference on Service-Oriented Computing, ICSOC 2011, held in Paphos, Cyprus, in December 2011. The 54 revised papers presented were carefully reviewed and selected from 184 submissions. The papers are organized in topical sections on business process modeling, quality of service, formal methods, XaaS computing, service discovery, service security and trust, service runtime infrastructures and service applications.